PENGARUH ORIENTASI KEWIRAUSAHAAN, ORIENTASI PASAR DAN LOW COST STRATEGY TERHADAP KINERJA PEMASARAN INDUSTRI KECIL MENENGAH (IKM) IKAN KERING DI KABUPATEN PASAMAN BARAT - Elondri, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
Research reveals initials How does Entrepreneurship Orientation, Market Orientation And Low Cost Strategy And Operations simultaneous partial Against PERFORMANCE BY Marketing using using the method of data collection and use of questionnaires That Form The method used is descriptive analysis and multiple regression analysis.Initial research requires speed, expandabilas OBJECT SME Research showed to the perpetrator of dried fish in West Pasaman and data collecting primary data and secondary data WITH THE using methods Namely Entire Population census as respondents were 105 Performers HPI dried fish in West Pasaman. Data Management using multiple regression WITH SPSS version 20.Results variable entrepreneurial orientation, market orientation and low cost strategies simultaneously operates a significant positive effect and boarding costs sunset Against SME Marketing dried fish in West Pasaman. SIBOR variable amount of influence could be seen from the findings of SPSS Namely adjusted R Square WITH Value 0267. Contributions SIBOR free prepaid variable on the dependent variable sum of 0.267, OR 26.7%, the remaining 73.3% 0733 OR influenced Posted variables studied NOT lie Its like Creativity Program Marketing, Innovation, Product QUALITY, customer orientation, differentiation strategy development and strategy development focus. Variable Operating entrepreneurial orientation partially significant and boarding costs sunset Against SME Marketing dried fish in West Pasaman, variable significant positive effect Market Orientation And Against boarding costs SME Marketing sunset dried fish in West Pasaman, variable while the low-cost strategy has positive effect but NOT Against significant boarding costs SME Marketing sunset dried fish in West Pasaman.Finally the authors suggest that SMEs Actors dried fish in West Pasaman Hobbies increase variable entrepreneurial orientation and market orientation in order to able to increase the boarding costs sunset Marketing. For researchers and lay CAN continue research in order to limitations hearts husband husband Research CAN enhanced.